Anionic redox in a-(Mo3S11)n polymer cathode for all-solid-state Li-ion battery. (1st February 2020) - Truong, Quang Duc; Yin, Li-Chang; Hung, Nguyen T.; Nguyen, Duc N.; Gambe, Yoshiyuki; Nayuki, Keiichiro; Sasaki, Yoshikazu; Kobayashi, Hiroaki; Saito, Riichiro; Tran, Phong D.; Honma, Itaru
Abstract: Lithium-ion battery that consists of a cathode made of (Mo3 S11 )n polymer and an anode of Li metal exhibits a high gravimetric-capacity, 673.3 mAh g −1 . A flexible structure of the (Mo3 S11 ) n polymer enables consecutive redox reactions of the S2 2− dimer and the Mo atoms. According to X-ray absorption near-edge spectroscopy, X-ray photoelectron spectroscopy and Raman spectroscopy, the chemical bonds of Mo–S and S–S in the polymer elongate by accepting electrons up to 16, while the Mo–Mo bond does not change much during the redox reactions. Although the polymer cathode is put in a solid-state electrolyte, the S2 2− dimer that is redoxed by the reaction of S2 2−  + 2e − → 2S 2− forms Li–S–Li bonds, which is an origin of the high capacity of the battery. The redox reactions in the (Lix Mo3 S11 )n polymer cathode is theoretically confirmed by first principles calculation. Graphical abstract: Image 1